Localization of Lesion Cells and Targeted Mitochondria Via Embedded Hydrogel Microsphere using Heat Transfer Microneedles. (22nd March 2023) - Lin, Feng; Zhuang, Yaping; Xiang, Lei; Ye, Tingjun; Wang, Zhen; Wu, Longxi; Liu, Yupu; Deng, Lianfu; Cui, Wenguo
Abstract: The localization of lesion cells and targeted regulation of organelle function can promote the lesion repair. However, conventional regulation is difficult to reach deep lesions and target mitochondria. In this study, dynamic spiral Mosaic technology is ued to construct heat transfer microneedles with spiral Mosaic micro/nano hydrogel microspheres (ST‐needle), using molecular chain motion in response to heat stimulation to regulate the adhesion of non‐oriented triblock polymer, as a dual delivery system for heat energy and biological factors. The ST‐needle system use its physical property to accurately reach the deep lesions and transfer heat to the lesion cells. Heat activates the dynamic spiral Mosaic mechanism of the ST‐needle system, removing the Mosaic state of hydrogel microspheres and realizing the arrival of heat and hydrogel microspheres into lesion together. Through the rapid inhibition of mitochondrial apoptosis by heat, and long‐term induce mitophagy by hydrogel microspheres releasing biological factors, finally complete the synergistic targeted regulation of mitochondrial function. In vitro/vivo experiments show that ST‐needle system can inhibit chondrocyte apoptosis more effectively (64.41% lower than conventional regulation). Based on dynamic spiral Mosaic technique and the synergistic regulation of heat and biological factors, the ST‐needle system is a promising method for lesion repair. Abstract : Dynamic spiral Mosaic technology to construct heat transfer screw‐threaded microneedles with micro/nano hydrogel microspheres, using molecular chain motion in response to heat stimulation to regulate the adhesion of non‐oriented polymer, as a dual delivery system for heat energy and biological factors, and complete the synergistic regulation of mitochondrion. The system is a promising method for regulatory organelle and lesion repair.